2022
DOI: 10.3389/fcomm.2022.910952
|View full text |Cite
|
Sign up to set email alerts
|

Unguided virtual-reality training can enhance the oral presentation skills of high-school students

Abstract: Public speaking is fundamental in our daily life, and it happens to be challenging for many people. Like all aspects of language, these skills should be encouraged early on in educational settings. However, the high number of students per class and the extensive curriculum both limit the possibilities of the training and, moreover, entail that students give short in-class presentations under great time pressure. Virtual Reality (VR) environments can help speakers and teachers meet these challenges and foster o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 81 publications
3
6
0
Order By: Relevance
“…The most beneficial effects were found for supportive audience behavior. These results add to the existing evidence on efficacy of a Virtual Reality on public speaking performance 4 , 5 and highlight the role of social feedback and audience behavior in virtual settings.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The most beneficial effects were found for supportive audience behavior. These results add to the existing evidence on efficacy of a Virtual Reality on public speaking performance 4 , 5 and highlight the role of social feedback and audience behavior in virtual settings.…”
Section: Discussionsupporting
confidence: 63%
“…As a result, course instructors might have focused more on verbal parameters and less on non-verbal aspects, such as gestures or body posture to evaluate speaker confidence. While, face-to-face situations might provide enriched information, it should be noted that a previous study found a specific improvement in vocal parameters by public speaking training and that this aspect was preserved in the digital format of the seminars 5 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies have empirically examined VRPST (Poeschl, 2017;Palmas et al, 2019;Boetje and Ginkel, 2021;Valls-Ratés et al, 2022). The results are promising, as previous research suggests that VRPSTs are effective, at least under certain circumstances.…”
Section: Introductionmentioning
confidence: 96%
“…There are various types of VRPST targeting different user groups. For instance, there are VRPST programs tailored to specific age groups, such as children (Sülter et al, 2022), high-school students (Valls-Ratés et al, 2022), or adults. Additionally, VRPST programs differ in terms of their intended objectives, tasks (e.g., presentation, lecture, explanation), and environments (e.g., boardrooms, large auditoriums, and classrooms; see (Takac et al, 2019).…”
Section: Introductionmentioning
confidence: 99%